Mona Saudi, Filwa Nazer - Khazindar, Mona 1959- (Misk Art Institute, 2024)
"Mona Saudi, Filwa Nazer: Discovering Arab Artists. The eleventh and twelfth volumes of The Art Library, a pioneering art volumes series that documents the most important modern and contemporary Arab artists. These gorgeously designed volumes offer an informal yet detailed introduction to the most prominent figures of Arab art. The collection is characterized by medium size books, each one dedicated to a single artist, richly illustrated and rigorously documented. The publications, presented in English and Arabic editions, are launched seasonally, in spring and fall, two by two, in a sophisticated cardboard slipcase. Each slipcase presents a Saudi alongside a non-Saudi artist."--Rizzoli, https://www.rizzoliusa.com/book/9788891839909/, viewed 04/02/2025
Issued in pair in slipcase
Title from slipcase
"Misk Art Institute" and it's logo on slipcase and on title page or cover of each volume
Keywords: Saʻūdī, Muná / Criticism and interpretation; Nazer, Filwa / Criticism and interpretation; Art, Arab / 21st century / Catalogs; Art, Jordanian / 21st century; Art, Saudi Arabian / 21st century; Sculpture / Jordan / 21st century; Artists / Saudi Arabia / Biography; Artists / Jordan / Biography; Artists / Arab countries / Biography; Art, Arab / 21st century; Artists / Saudi Arabia; Art arabe / 21e siècle; Artistes / Arabie saoudite; Art saoudien / 21e siècle; Art arabe / 21e siècle / Catalogues; Art jordanien / 21e siècle; Artistes / Arabie saoudite / Biographies; Artistes / Jordanie / Biographies